GAMBARAN KEMAMPUAN MASTIKASI PADA PASIEN PENGGUNA GIGI TIRUAN PENUH DI RUMAH SAKIT GIGI DAN MULUT UNIVERSITAS SAM RATULANGI MANADO - Panjaitan, Yuniar P.; Ticoalu, Shane H. R.; Siagian, Krista V. (e-GiGi, 2016)
Abstract: Full dentures are made for people with missing teeth entirely. One of the objectives of full denture usage is to improve and enhance the function of mastication. Mastication is a process of pulverizing food to be swallowed and digested. This study aimed to assess the mastication ability of patients with full denture made at Dental Hospital of the University of Sam Ratulangi Manado. This was a descriptive observational study with a cross sectional design. There were 56 respondents in this study obtained by using total sampling method. Respondents were patients with full dentures made at the Dental Hospital University of Sam Ratulangi during January 2014 - December 2015. The instrument consisted of questionnaires about mastication ability. Data were processed and analyzed descriptively then were presented in tables. The results showed that 60.71% of respondents had good ability of mastication. Conclusion: The mastication ability of patients with full denture at the Dental Hospital of the University of Sam Ratulangi was in good categoryKeywords: full denture, mastication, the ability of masticationAbstrak: Gigi tiruan penuh dibuat untuk penderita kehilangan gigi seluruhnya yang bertujuan antara lain untuk memperbaiki dan meningkatkan fungsi mastikasi. Mastikasi merupakan proses melumatkan makanan untuk ditelan dan dicerna. Penelitian ini bertujuan untuk menilai kemampuan mastikasi pasien pengguna gigi tiruan penuh di Rumah Sakit Gigi dan Mulut Universitas Sam Ratulangi Manado. Jenis penelitian ialah deskriptif observasional dengan desain potong lintang. Terdapat 56 responden yang diperoleh dengan metode total sampling yaitu pasien yang membuat gigi tiruan penuh di Rumah Sakit Gigi dan Mulut Universitas Sam Ratulangi periode Januari 2014-Desember 2015. Instrumen penelitian berupa kuesioner mengenai kemampuan mastikasi. Data yang diperoleh diolah dan dianalisis secara deskriptif kemudian disajikan berdasarkan distribusi dalam bentuk tabel. Hasil penelitian menunjukkan bahwa 60,71% responden memiliki kemampuan mastikasi yang baik. Simpulan: Kemampuan mastikasi pasien pengguna gigi tiruan penuh di Rumah Sakit Gigi dan Mulut Universitas Sam Ratulangi dalam kategori baik.Kata kunci: gigi tiruan penuh, mastikasi, kemampuan mastikasi